Genomic Landscape of Uterine Sarcomas Defined through Prospective Clinical Sequencing - Hensley, Martee L. (Clin Cancer Res, 2020)
PURPOSE: We examined whether prospective molecular characterization of advanced metastatic disease can reveal grade and/or histology-specific differences to inform diagnosis and facilitate enrollment onto clinical trials. EXPERIMENTAL DESIGN: Patients with uterine sarcoma consented to a prospective study of next-generation sequencing (NGS). Clinical annotations were extracted from their medical record. Tumor and matched normal DNA were subjected to NGS, and the genomic landscape was explored for survival correlations and therapeutic targetability. RESULTS: Tumors from 107 women were sequenced and included leiomyosarcoma (uLMS, n=80), high-grade non-LMS (n=22), low-grade endometrial stromal sarcoma (LG-ESS, n=4), and smooth muscle tumor of uncertain malignant potential (STUMP, n=2). Genomic profiling influenced histologic diagnosis in three cases. Common uterine LMS (uLMS) alterations were loss-of-function mutations in TP53 (56%), RB1 (51%), and ATRX (31%). Homozygous deletions of BRCA2 were present in 5% of these patients. PTEN alteration frequency was higher in the metastases samples as compared to the primary samples. Genomes of low-grade tumors were largely silent, while 50.5% of high-grade tumors had whole genome duplication. Two metastatic uLMS cases were hypermutated. Both had prolonged disease-free survival. Potentially actionable mutations were identified in 48 patients (45%), eight (17%) of whom received matched therapy with two achieving clinical responses. Among uLMS patients with somatic BRCA2 alterations, sustained partial responses were observed with PARP inhibitor-containing therapy. DISCUSSION: Prospective genomic profiling can contribute to diagnostic precision and inform treatment selection in patients with uterine sarcomas. There was evidence of clinical benefit in uLMS patients with somatic BRCA2 alterations treated with PARP inhibitors.